THE ROLE OF SENIOR CITIZEN’S COMMITTEES (WADIHITY SAMITHI) IN ERADICATING NEW FORM OF POVERTY (Proceedings of the International Conference on Poverty and Sustainable Development, 2018)
The last two national censuses in Sri Lanka demonstrate a transformation in the population structure of the country. The current proportion of elderly population in Sri Lanka is higher than the proportion in other South Asian countries. The concept of senior citizens’ committee is implemented by the government under the Protection of the Rights of Elders Act, No 9 of 2000 with the active participation of the community sector. This study examined the contribution of Senior Citizen committees in addressing socioeconomic needs of the elderly within their own local community. The assumption was that they were mostly unable to meet many of their financial needs within the family system due to a range of reasons and as a result, dependency, abuses and emotional suffering etc. have been characteristic facts in their daily living. The study was conducted in Kahatagasdigiliya Divisional Secretariat (DS) Division and looked at how the conducive socio-cultural and recreational environment within Senior Citizen Societies contributes to active economical participation. Purposive sampling was used to get insights in this regard by applying both quantitative and qualitative research methods. The committees promote and provide opportunity for lifelong learning and active ageing so people can be active and resilient, stay connected and increase their economic wellbeing, especially in independency. Community resources are not enough to support the societies and also it has not been the community priority for their limited resources.
Keywords: Senior Citizen’s Committees; Elder Rights; Poverty Eradication; Active Aging